Dramaturgia muzyczna - Wąchocka , Ewa (Przestrzenie Teorii, 2021)
In her paper, Ewa Wąchocka examines the phenomenon of recent dramatic works becoming increasingly more ‘musical’ and the terminological shift it brought about, i.e. the inclusion of the term ‘musical dramaturgy’ in writing for the stage. The author argues that far from being limited to the sounds of speech and language in general, musicality also encompasses a variety of non-musical sounds, the unravelling of the play’s narrative and the psychological makeup of its characters; it also penetrates deeply into the structure of the text. In the analysis of plays by W. Murek, A. Grzegorzewska, and S. Bogacz, the author demonstrates how essential the inspirations sourced from musical culture are for recent dramatic works: the 20th-century experiments with music, the discovery of how potent sound expression can be, or the most technologically advanced methods of sound reproduction. By presenting the many and varied dramatic strategies, the author shows that contemporary playwrights not only use musicality to represent the sound landscape of the world but, first and foremost, to create the ontology of an internally conflicted world.